The influence of moral identity on green consumption - Li, Dalin; Cheng, Guo; Wang, Chunya (Frontiers in Psychology, 2022)
Existing studies show that moral identity promotes green consumption, but its influence mechanism and boundary conditions remain unidentified. However, moral identity includes internalization and symbolization, which affect green consumption in different ways. Advertising goal framing also has an impact on green consumption. Existing studies often focus on moral identity internalization but neglect the role of moral identity symbolization and fail to fully consider the interaction, mechanism, and boundary conditions between moral identity and advertising goal framing. This study assumes that advertising goal framing includes both intrinsic and extrinsic goals. We attempt to verify the combined influence of internalization and symbolization of moral identity, advertising goal framing, and moral awareness on green purchasing intention. Through two experiments, we found that (1) the internalization and symbolization of moral identity can promote consumers’ green purchasing intention; (2) consumers with high internalization of moral identity have more positive responses to intrinsic goal advertising; and (3) moral awareness can enhance the combined influence of moral identity internalization and intrinsic goal advertising on consumers’ green purchasing intention; and (4) self-consistency and social approval mediate the combined impact of moral identity and advertising goal framing on consumers’ green purchasing intention. This study enriches the literature on the influence of moral identity on green consumption. Businesses can also draw on these findings to improve the effectiveness of green marketing.